PENGARUH KUALITAS PRODUK, PENGETAHUAN LINGKUNGAN, SIKAP LINGKUNGAN DAN KESADARAN LINGKUNGAN TERHADAP MINAT BELI PRODUK BERKELANJUTAN (Produk Sepeda Motor Listrik di Kota Yogyakarta) - Sisrika, Sisrika; Prasojo, Eko (Journal Competency of Business, 2024)
This study is titled "The Influence Of Product Quality, Environmental Knowledge, Environmental Awareness, And Environmental Attitude On Purchase Intention Of Sustainable Products (Electric Motorcycle Products in Yogyakarta City)". This study aims to analyze the influence of product quality, environmental knowledge, environmental awareness, and environmental attitude on the purchase intention of electric motorcycles in Yogyakarta City. The research was conducted using a survey method using a questionnaire as a data collection tool. The population in this study was the people of Yogyakarta City who have an interest in buying electric motorcycles. The sample was selected using a purposive sampling technique with the criteria of respondents who have an interest in electric motorcycle products. Data analysis using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that product quality had a positive and significant effect on purchase intention with a coefficient of 0.381, a T-Statistic value of 4.448 (>1.96) (p<0.05). Environmental knowledge with a coefficient of 0.102, a T-Statistic value of 1.063 (<1.96) (p>0.05) and environmental attitude with a coefficient of 0.165, a T-Statistic value of 1.244 (<1.96) (p>0.05) did not affect the purchase intention of electric motorcycles in Yogyakarta City. And environmental awareness also significantly and positively affects purchase intention with a coefficient of 0.331, a T-Statistic value of 3.283 (>1.96) (p<0.05). These findings indicate that the better the product quality and the higher the consumer's environmental awareness, the more it will increase their purchase intention for electric motorcycle products.